2020
DOI: 10.3329/jss.v23i1.44239
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and Antibiotic Resistance Pattern of Bacteria Causing Urinary Tract Infections (UTI) in a Tertiary Care Hospital

Abstract: Background: Urinary tract infection (UTI) is one of the most common bacterial infections encountered by clinicians particularly in developing countries. Current knowledge on antimicrobial resistance pattern is essential for appropriate therapy. The aim of the present study was to identify the causative organisms for UTI and to determine the antibiotic susceptibility pattern of organisms causing UTI. Method: This cross sectional study was carried out in the department of Microbiology, Sir Salimullah Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
0
4
2
Order By: Relevance
“…A study done in Bangladesh reported the prevalence of Klebsiella species, Pseudomonas species and Proteus species were 1.9%, 7.9% and 7.2% respectively and these finding did not correlate with our study 29 . In contrary to our observation, various studies done in different countries reported Klebsiella species as second most common isolate 8,11,25,30 species and Enterococcus species were 12%, 7% and 6% respectively and these observation did not match with our findings 32 .…”
Section: Table -V: Antimicrobial Sensitivity Pattern Of Gram Positive Isolates (N=222) Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…A study done in Bangladesh reported the prevalence of Klebsiella species, Pseudomonas species and Proteus species were 1.9%, 7.9% and 7.2% respectively and these finding did not correlate with our study 29 . In contrary to our observation, various studies done in different countries reported Klebsiella species as second most common isolate 8,11,25,30 species and Enterococcus species were 12%, 7% and 6% respectively and these observation did not match with our findings 32 .…”
Section: Table -V: Antimicrobial Sensitivity Pattern Of Gram Positive Isolates (N=222) Discussioncontrasting
confidence: 95%
“…In contrary to our finding, higher growth rate was observed in other studies done in Bangladesh by Haque et al, (42.66%) and in India by Mishra et al, (43.61%) 27,28 . In our study, the rate of growth was relatively low in comparison to above two studies and the reason might be due to prior antibiotic therapy before submitting the urine sample, incomplete dose of antibiotic and clinical conditions like non gonococcal urethritis or other conditions that mimic UTI 29 .…”
Section: Table -V: Antimicrobial Sensitivity Pattern Of Gram Positive Isolates (N=222) Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Even though among the collected samples, urine was the highest in number, it yielded only 19% growth. A study done in a tertiary hospital in Bangladesh from outdoor and indoor sample it yielded similar result where 20.1% showed significant growth of bacteria (Afroze et.al, 2019).…”
Section: Discussionmentioning
confidence: 81%